Prevalencia y factores influyentes del síndrome de Burnout en el personal docente del Instituto Beatriz Cueva de Ayora en el periodo 2015-2016. - Machuca Córdova, Liliana Maribel (2016)
This research aims, to determine the prevalence and influencing factors of burnout syndrome in teachers of the Institute Beatriz Cueva de Ayora To fulfill this research, a cross-sectional, descriptive, quantitative approach with a sample composed of 100 teachers, Beatriz Cueva de Ayora who met the inclusion criteria Institute was used. To conclude the following: The prevalence of burnout syndrome was 15%; in the subscales, we found an average 48% for emotional exhaustion, level under 48% for depersonalization and high 70% for personal achievement level, so according to levels of burnout in our research, not the syndrome is defined, but well only at risk for acquiring burnout syndrome. Also within personal risk factors, the most affected age group 51-60 years were the high level of emotional exhaustion and high depersonalization 60% to 45%, the highest prevalence was found in teachers who are single , showing them both high emotional exhaustion and depersonalization 57% to 54%. As for the most prevalent occupational characteristics is present in the seniority corresponding (6-10 years) presented Burnout level of 73% and those working more than 30 hours with 76% Keywords: Illnesses, Burnout Syndrome, Secondary Teachers